Step-by-step explanation:
(5√2-4√3)(5√2-4√3)=
(5√2-4√3)^2=(5√2)^2+(4√3)^2-2(5√2)(4√3)
=25*2+16*3-10√2*4√3
=50+48-10√2*4√3
=98-10√2*4√3 is the answer
Answer:
11/9 or 1 2/9
Step-by-step explanation:
2/3 multiples by 3 in both the numerator and denominator is equal to 6/9. 6/9 plus 5/9 is 11/9. you want to make sure the denominator is the same before adding or subtracting
Answer:
B and C, only
Step-by-step explanation:
Answer: oh should we not look for it haha you just got burned
Step-by-step explanation: